UJI TEKANAN DAN DAYA SERAP AIR PADA BATAKO BERBAHAN DASAR CAMPURAN LIMBAH STYROFOAM, SERAT KELAPA, DAN ABU GOSOK - Andreansyah .; Rahma Rosaliana Saraswati; Ersa Ayu Lestari (Risenologi, 2019)
The aim of the research is to produce an environmentally friendly brick and also know the pressure and water absorption of the concrete- based concrete mixture of styrofoam waste, coconut fiber, and rubbing ash. The method used in this research is quantitative experimental research method. Based on the test results, it can be concluded that in order to achieve maximum pressure the composition of the waste should be 25% and to achieve the minimum absorption, the composition of the waste should be 50%. Batako with a waste composition of 25% and 50% can be categorized as suitable for use based on the results of compressive strength and water absorption. Meanwhile, concrete blocks with 75% waste are not suitable for use because the results of pressure testing are below the minimum standard SNI No. 03-0349 in 1989.